(untitled) (Nigerian Journal of Technology, 2003)
Using Simplex method and Scheffe’s experimental design, the bending strength, water absorption capacity and other properties of titles from two Nigerian clays were investigated for the whole range of imposition recommended in literature. One of the days from Nsu was found suitable for tile production and the region of application was indicated. The optimal rational composition was found to be: Nsu Clay = 47.8%, quartz = 33.7% and CaCO3 = 18.5%. The other clay from Ukpor was found unsuitable at the firing temperature (l000°C) used. It showed bending strength lower than the standard requirement for all compositions studied. To improve the strength an increase in firing temperature is recommended.